Neglected human Rickettsia felis infection in Taiwan: A retrospective seroepidemiological survey of patients with suspected rickettsioses. - Wan-Hsiu Yang; Meng-Shiuan Hsu; Pei-Yun Shu; Kun-Hsien Tsai; Chi-Tai Fang (Public Library of Science (PLoS), 2021)
Background Current knowledge on Rickettsia felis infection in humans is based on sporadic case reports. Here we conducted a retrospective seroepidemiological survey of R. felis infection among febrile patients visiting a medical center in Taipei. Methodology/principal findings A total of 122 patients with suspected rickettsioses presenting with fever of unknown origin (FUO) but tested negative for scrub typhus, murine typhus, or Q fever were retrospectively identified during 2009 to 2010. The archived serum samples were examined for the presence of antibodies against R. felis, Rickettsia japonica, and Rickettsia typhi using microimmunofluorescence (MIF) assay. Serological evidence of Rickettsia exposure was found in 23 (19%, 23/122) patients. Eight patients had antibodies reactive to R. felis, including four with current infection (a ≥4-fold increase in IgG titer between acute and convalescent sera). The clinical presentations of these four patients included fever, skin rash, lymphadenopathy, as well as more severe conditions such as pancytopenia, hepatomegaly, elevated liver enzymes/bilirubin, and life-threatening acute respiratory distress syndrome. One of the patients died after doxycycline was stopped after being tested negative for scrub typhus, Q fever, and murine typhus. Conclusions Rickettsia felis is a neglected flea-borne pathogen in Taiwan, and its infection can be life-threatening. Further prospective studies of the prevalence of R. felis among patients with FUO and compatible clinical manifestations are warranted.